Makna Teologis dan Implementasi Perintah “Menjauhkan Diri dari Percabulan’’ Eksegesis 1 Korintus 6:18 dalam Kehidupan Kristen Kontemporer - Durmia Sinta Tarihoran; Yanto Paulus Hermanto (Kharisma: Jurnal Ilmiah Teologi, 2026)
Abstract This study examines the theological meaning and implementation of the command to “flee from sexual immorality” based on the exegesis of 1 Corinthians 6:18 in contemporary Christian life. The study is grounded in the growing normalization of sexual immorality, digital pornography, and permissive culture, which weaken the witness of Christian faith. This research employs a qualitative method through literature review using historical-grammatical and theological-contextual approaches. The findings show that the command to flee from sexual immorality is absolute, immediate, and continuous because the believer’s body is the temple of the Holy Spirit and belongs to Christ. Its implementation involves three dimensions: personal, by guarding the mind, heart, and body; communal, through Christian sexuality education, discipleship, and spiritual discipline; and social, through holy living as a witness amid permissive culture. This study affirms that bodily holiness is an expression of obedience, worship, and contemporary Christian witness. Abstrak Penelitian ini membahas makna teologis dan implementasi perintah “menjauhkan diri dari percabulan” berdasarkan eksegesis 1 Korintus 6:18 dalam kehidupan Kristen kontemporer. Latar belakang penelitian ini adalah meningkatnya normalisasi perilaku seksual menyimpang, pornografi digital, dan budaya permisif yang melemahkan kesaksian iman orang percaya. Penelitian menggunakan metode kualitatif melalui studi pustaka dengan pendekatan historis-gramatikal dan teologis-kontekstual. Hasil kajian menunjukkan bahwa perintah “larilah dari percabulan” bersifat mutlak, segera, dan berkelanjutan karena tubuh orang percaya adalah bait Roh Kudus dan milik Kristus. Implementasinya mencakup tiga dimensi: pribadi, melalui penjagaan pikiran, hati, dan tubuh; komunal, melalui pendidikan seksualitas Kristen, pemuridan, dan disiplin rohani; serta sosial, melalui kesaksian hidup kudus di tengah budaya permisif. Penelitian ini menegaskan bahwa kekudusan tubuh merupakan bentuk ketaatan, ibadah, dan kesaksian iman Kristen masa kini.